Forensic Features of Lethal Late‐Presenting Diaphragmatic Hernias. Issue 5 (22nd June 2016) - Thompson, Melissa; Wills, Stephen; Byard, Roger W.
Abstract: Diaphragmatic defects are a relatively common and benign finding in adults which may be congenital or secondarily acquired. The case files at Forensic Sciences South Australia were reviewed over a 10‐year period from July 2005 to June 2015 for all adult (>17 years) cases in which diaphragmatic hernias were identified at postmortem examination that had either caused or contributed to death. Five cases were found: age range 49–90 years (average 67.2 years); male:female ratio 2:3. Herniated organs included the stomach ( N = 3), small ( N = 3) and large intestines ( N = 2). Mechanisms of death involved lung compression with respiratory failure and/or mediastinal shift, and vascular compromise with gastric or intestinal infarction and/or perforation. Diaphragmatic hernias may not be identified until the time of autopsy and may be quite complex entities to evaluate due to a lack of clinical history and to difficulties in determining their origin and possible contributions to mechanisms of death.